2013
DOI: 10.1038/sc.2013.10
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and treatment profiles of spinal cord injury in southeast Nigeria

Abstract: Study design: Retrospective study. Objective: To evaluate the epidemiology and treatment outcome of spinal cord injuries (SCIs) at three tertiary care centres within southeast Nigeria. Setting: Southeast Nigeria. Methods: Causes, seasonal variation, transportation to hospital, severity of injury, treatment and outcome of patients with SCIs treated by the authors at three study locations from September 2009 to August 2012 were studied. Results: Eighty-five patients with SCI had been admitted during that period … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
35
4
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 16 publications
6
35
4
2
Order By: Relevance
“…This differs from the Nigerian study, where it was found that farmers were the fifth most common occupation group who suffered from SCI (Nwankwo and Uche, 2013).…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…This differs from the Nigerian study, where it was found that farmers were the fifth most common occupation group who suffered from SCI (Nwankwo and Uche, 2013).…”
Section: Discussioncontrasting
confidence: 53%
“…There were more men than women, with a ratio of 8:1. An epidemiological in Southeast Nigeria found that the male and female ratio was 4.3:1 and the 31-45 year age group was more frequently affected (Nwankwo and Uche, 2013). In North America the main cause of traumatic spinal cord injury (TSCI) was motor vehicles accident rather than fall from height (Mothe and Tator, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High and high-energy falls were more common (82.9%) than low falls (17.1%) in the current study. Falls from a significant height were also noted in many low and lower-middle income countries like India (Chhabra and Arora, 2012), Nepal (Lakhey et al, 2005), Pakistan (Rathore et al, 2008), and Nigeria (Nwankwo and Uche, 2013). Contrarily, low falls occurred more in middle and high-income countries where elderly people (>65 years) are a growing concern: China (Cheng et al, 2008), Australia (Tee et al, 2013), Finland (Koskinen et al, 2014), and Japan (Katoh et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have pointed out the seasonal occurrence of trauma. [26][27][28] The incidence of blunt chest injury is related to the number of motor vehicular accidents and thus the incidence is decreased with reduction in motor vehicular accidents. 2 and conversely, increased with increased motor vehicular accidents.…”
Section: Discussionmentioning
confidence: 99%